Shaping Scientific Worldview of Schoolchildren by Including Synergetics into the Content of Education - Bazarbek A. Mukushev (National Research Mordova State University, 2018)
Introduction. The article presents an optimal use of synergy elements as most important methods of forming a generalized worldview in schoolchildren. It determines the relevance of this study. A brief theoretical analysis of synergetic as a self-organization theory is given. The purpose of the article is to substantiate the efficiency of synergetics in the process of molding the worldview of high school s tudents. Materials and Methods. Pedagogical experiment method, test method, sign criterion method, analysis, comparison and generalization were used as research tools. Results. Methodological tools to enhance the formation of the system of ideological knowledge among students were identified. Elective courses are considered as an effective means of realizing the worldview functions of high school subjects. The results of the pedagogical experiment are presented. In the experiment levels of formation of the system of worldview knowledge in natural science and humanities were revealed. The authors used the ideas of synergetics in the process of forming the scientific worldview of students, who assimilated the knowledge holistically, but not in fragments. They got an integral view of reality and formed a synergetic picture of the world. Discussion and Conclusion. The practical significance of the research is in the introduction of ideas of synergetics into the educational process of secondary schools and the structuring the content of natural sciences and humanities. This content is aimed at the formation of a generalized worldview of schoolchildren. The novelty of the research lies in the development of integrative subjects, courses and interdisciplinary programs with synergistic content. This development allows you to prepare high-quality teaching staff. These frames are capable of realizing the ideological function of school subjects. Further development of the material presented in the article is seen in expanding the scope of research in these areas: designing a system of ideological and synergistic knowledge. This knowledge is necessary for the formation of the generalized worldview; development of methods and technologies for teaching a system of synergistic knowledge.